Solution for What is 67 percent of 6:

67 percent *6 =

(67:100)*6 =

(67*6):100 =

402:100 = 4.02

Now we have: 67 percent of 6 = 4.02

Question: What is 67 percent of 6?

Percentage solution with steps:

Step 1: Our output value is 6.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{6}={100\%}.

Step 4: Similarly, {x}={67\%}.

Step 5: This results in a pair of simple equations:

{6}={100\%}(1).

{x}={67\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{6}{x}=\frac{100\%}{67\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{6}=\frac{67}{100}

\Rightarrow{x} = {4.02}

Therefore, {67\%} of {6} is {4.02}

Solution for What is 6 percent of 67:

6 percent *67 =

(6:100)*67 =

(6*67):100 =

402:100 = 4.02

Now we have: 6 percent of 67 = 4.02

Question: What is 6 percent of 67?

Percentage solution with steps:

Step 1: Our output value is 67.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{67}={100\%}.

Step 4: Similarly, {x}={6\%}.

Step 5: This results in a pair of simple equations:

{67}={100\%}(1).

{x}={6\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{67}{x}=\frac{100\%}{6\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{67}=\frac{6}{100}

\Rightarrow{x} = {4.02}

Therefore, {6\%} of {67} is {4.02}